SAT0444 Administration of Routine Preventative Vaccinations in Children with Juvenile Idiopathic Arthritis Receiving Adalimumab. (23rd January 2014) - Mozaffarian, N.; Karunaratne, M.; Arora, V.
Abstract : Background: Adalimumab, a fully human monoclonal antibody to tumor necrosis factor-alpha (TNF) has been shown to be safe and effective in juvenile idiopathic arthritis (JIA), and is approved for this use in several countries. 1 Objectives: Patients with JIA are candidates for routine childhood vaccinations. This post hoc report describes the observed use of vaccines in JIA patients receiving adalimumab for up to 4 years in a clinical trial setting. Methods: Patients with active JIA were enrolled in one of the following trials: M10-444 (ages 2-4 or ≥ age 4 weighing <15 kg in US, EU), M10-240 (ages 4-17 in Japan), or DE038 (ages 4-17 in US, EU). Patients received treatment with ADA (weight-based dosing) every other week, either with or without methotrexate use. Any vaccinations administered were based on the judgment of the study investigators. Descriptive statistics were used to summarize all vaccinations, including influenza vaccine. Adverse events (AEs) related to active influenza virus infection were collected by a predefined MedDRA Query, and events occurring within 270 days of influenza vaccination were identified. Results: A summary of all vaccinations is presented in the Table . Among the different types of vaccines, the most frequently administered were: influenza virus vaccine polyvalent in DE038 and M10-240 (n=59 and 63 vaccinations, respectively), and pneumococcal in M10-444 (n=28 vaccinations). In DE038 and M10-240, 2 patients each received >5 vaccinations and in M10-444, 10 patients received >5 vaccinations. The majority of vaccinated patients in each study received >1 type of vaccination. However, influenza vaccine was administered to only 34/171 (20%), 20/25 (80%), and 4/32 (13%) of children during the course of the study in DE038, M10-240, and M10-444, respectively, and the mean (SD) time to 1st influenza vaccination was high: DE038, 675 (618) days; M10-444, 189 (80) days, and M10-444, 83 (76) days. Conclusions: These data support the idea that JIA patients treated with adalimumab can be safely immunized with routine, inactive, preventative vaccines, including influenza vaccine. However, based on the CDC recommended schedule, not all of the eligible children were vaccinated, suggesting that physicians may be reluctant to use vaccines in children receiving antirheumatic therapies. Further investigation regarding rheumatologists' vaccination practices for patients with JIA is warranted. References: Lovell DJ, et al. NEJM 2008;359:810-820. Acknowledgements: Douglas E. Dylla, Ph.D., AbbVie Inc., for abstract preparation. Disclosure of Interest: N. Mozaffarian Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., M. Karunaratne Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., V. Arora Shareholder of: AbbVie Inc., Employee of: AbbVie Inc.